2022
DOI: 10.3390/foods11101437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Konjac Glucomannan on Oil Absorption and Safety Hazard Factor Formation of Fried Battered Fish Nuggets

Abstract: The purpose of this study was to investigate the effects of konjac glucomannan (KGM) on oil absorption and the formation of safety hazard factors in fried battered fish nuggets by measuring advanced glycation end products (AGEs) and acrylamide contents. Other physicochemical properties were determined to explore the reason for oil absorption and formation of safety hazard factors. The acrylamide was found mainly in the crust. The addition of 0.8% KGM could significantly reduce the acrylamide content (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Water molecules would be bound within the network structure and lose their mobility while inhibiting oil absorption [73]. Sun et al [74] reported that the addition of konjac glucomannan significantly reduced the AGEs and acrylamide contents of fried fish nuggets.…”
Section: Safety Hazard Factor Suppressionmentioning
confidence: 99%
“…Water molecules would be bound within the network structure and lose their mobility while inhibiting oil absorption [73]. Sun et al [74] reported that the addition of konjac glucomannan significantly reduced the AGEs and acrylamide contents of fried fish nuggets.…”
Section: Safety Hazard Factor Suppressionmentioning
confidence: 99%
“…Более того, физическими и механическими свойствами таких продуктов можно управлять в зависимости от физикохимической природы пленки, образующейся под слоем панировочной матрицы [13]. Данными свойствами обладает достаточно большое разнообразие пищевых ингредиентов: животные белки и растительные белки, производные целлюлозы и различные камеди [18,55]. Сообщается, что дополнительными механизмами, ингибирующие абсорбцию жира белками и гидроколлоидами, кроме образования пленки, являются повышение гидрофильности поверхности и гелеобразование при нагревании [60].…”
Section: способы уменьшения поглощения маслаunclassified
“…Currently, scientists' studies on the inhibition of AGEs in fried food mainly focus on optimising food processing (Han et al, 2022), modification of raw materials (Bai et al, 2023;Chu et al, 2023), and the addition of exogenous substances (Zhao et al, 2022;Wang et al, 2023). In recent years, it has been found that air frying (Gao et al, 2023a), batter coating (Sun et al, 2022), and film coating (Gao et al, 2023b) have significant impacts on the inhibition of AGEs in fried fish cakes. However, these methods suffered from the disadvantages of cumbersome processing steps, higher costs, and poorer sensory properties.…”
Section: Introductionmentioning
confidence: 99%